Persepsi Masyarakat Rw 05 Karang Asem Barat Citeureup Kabupaten Bogor Terhadap Program Tanggung Jawab Sosial Lingkungan - Hasan, Syahirah; Nugroho, David Rizar; Hafzotillah, Hafzotillah (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2024)
This research aims to determine the perception of the RW 05 community towards the environmental social responsibility program of PT Argha Karya Prima Industri Tbk. The independent variable (X1) is individual characteristics, (X2) environmental social responsibility and the dependent variable (Y) is community perception. The indicators used are individual characteristic variables, gender, age, marital status, number of dependents. And indicators of environmental social responsibility (X2) are health, economy, socio-culture. Meanwhile, indicators of public perception include cognitive, affective and conative. This research was carried out in RW 05, Karang Asem Barat sub-district, Citeureup sub-district, Bogor regency. This research uses a descriptive approach with quantitative methods. The sampling technique uses non-probability sampling with the criteria of the RW 05 community. The data collection technique is by distributing questionnaires to 80 respondents and observing. The results found that there was a relationship between environmental social responsibility programs and community perceptions. Respondents felt fulfilled by the TJSL program which was clear and responsible for the environment. Environmental social responsibility programs with economic indicators have a real and significant relationship with affective variables. From these results it can be clearly seen that the influence is unidirectional or positive